Versatile SMAD2 and SMAD3 epitope–tagged mouse models for genomic profiling of TGFβ signaling: Uncovering GDF9–SMAD2/3 targets - Zian Liao; Qian Zhang; Keisuke Shimada; Kaori Nozawa; Suni Tang; Masahito Ikawa; Diana Monsivais; Martin M. Matzuk (Proceedings of the National Academy of Sciences, 2026)
Transforming growth factor β (TGFβ) signaling pathways are integral for a plethora of biological processes. SMAD2 and SMAD3 are the principal transcriptional effectors of TGFβ superfamily ligands, yet quantitative, genome-wide mapping of their DNA-associated complexes under physiological contexts has remained limited due to the lack of specific, robust models. Here, we generated two versatile epitope–tagged mouse models in which endogenous SMAD2 and SMAD3 proteins are globally tagged with hemagglutinin (HA) and podoplanin (PA) sequences, respectively, enabling high-fidelity profiling of SMAD2 and SMAD3 binding across tissues. To demonstrate the broad application of our models, we exemplified the usage of our lines in ovarian biology, where we defined the transcriptional programs downstream of GDF9, a key oocyte-derived ligand in folliculogenesis from the TGFβ superfamily. By integrating genomic and transcriptomic analyses, we identified direct genes induced by the GDF9-SMAD2/3 axis and identified gene sets suppressed by this signaling cascade, highlighting a previously underappreciated role of GDF9 in attenuating competing pathways to ensure proper ovarian granulosa cell fate transitions. Short-term GDF9 stimulation shifts SMAD2/3 cofactor recruitment toward lineage- and differentiation-associated transcription factors, without significant global changes in H3K27ac landscapes, indicating that GDF9 signals through targeted SMAD recruitment to preacetylated chromatin regions. Network analyses further demonstrated that GDF9-SMAD2/3 direct targets align with luteinizing hormone-driven preovulatory signaling. Together, our study generated epitope-tagged mouse models that provide extensive and applicable in vivo genetic toolkits for tissue-specific dissection of TGFβ family signaling and reveal a comprehensive, direct transcriptional network through which GDF9 coordinates granulosa cell differentiation and follicular maturation.